2008
DOI: 10.1111/j.1365-246x.2008.03777.x
|View full text |Cite
|
Sign up to set email alerts
|

Lithosphere of the Dharwar craton by joint inversion ofPandSreceiver functions

Abstract: S U M M A R YThe Archean Dharwar craton in south India is known for long time to be different from most other cratons. Specifically, at station Hyderabad (HYB) the Ps converted phases from the 410-and 660-km mantle discontinuities arrive up to 2 s later than in other cratons of comparable age, which implies lower upper mantle velocities. To resolve the unique lithosphere-asthenosphere system of the Dharwar craton, we inverted jointly P and S receiver functions and teleseismic P and S traveltime residuals at 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 49 publications
7
54
0
Order By: Relevance
“…The other sources are located at average depths of 43-45, 19 and 10-11 km representing Moho, lower crust and upper crustal sources, respectively. It is interesting to observe that the spectral depth to Moho (43-45 km), and the lower crust (19 km) is almost same as that inferred from various seismic studies (Kiselev et al, 2008;Reddy, 2010;Gupta et al, 2003). These seismic studies suggested crustal thickness largely varying from 34 to 55 km in different parts of the Indian shield.…”
Section: Spectrum Of Bouguer Anomaly Of Indiasupporting
confidence: 58%
See 1 more Smart Citation
“…The other sources are located at average depths of 43-45, 19 and 10-11 km representing Moho, lower crust and upper crustal sources, respectively. It is interesting to observe that the spectral depth to Moho (43-45 km), and the lower crust (19 km) is almost same as that inferred from various seismic studies (Kiselev et al, 2008;Reddy, 2010;Gupta et al, 2003). These seismic studies suggested crustal thickness largely varying from 34 to 55 km in different parts of the Indian shield.…”
Section: Spectrum Of Bouguer Anomaly Of Indiasupporting
confidence: 58%
“…Seismic results indicate that crustal thickness varies considerably, from 32 km under the EDC up to 55 km under the Western Dharwar Craton (WDC, Fig. 1) (Kiselev et al, 2008;Gupta et al, 2003). Deep seismic soundings have also suggested crustal thickness varying from 34 km under the EDC to 45-50 km under the SGT, the WDC and along the Himalayan front (Reddy, 2010).…”
Section: Introductionmentioning
confidence: 95%
“…Crustal thicknesses beneath stable cratons vary by more than 10-15 km, for instance beneath India [Gupta et al, 2003;Kiselev et al, 2008;Rai et al, 2005], Canada [e.g., Perry et al, 2002], and the Great Plains of the USA [Gilbert, 2012;Sheehan et al, 1995], as well as beneath Tibet [e.g., Tseng et al, 2009]. Again from (2), if uncompensated, such differences in crustal thickness would generate free-air and isostatic gravity anomalies approaching 200-300 mGal.…”
Section: "Residual" Topography and "Dynamic" Topographymentioning
confidence: 99%
“…They infer a ∼200-km-thick lithosphere beneath the Dharwar Craton and a mid-lithospheric low velocity region at a depth of ∼100 km. Kiselev et al (2008) jointly inverted both P and S receiver functions and teleseismic P and S traveltime residuals to resolve the lithosphere-asthenosphere boundary (LAB) of the Dharwar Craton at 10 seismograph stations. The most conspicuous feature of their study is the absence of a high velocity mantle keel (Vs ∼ 4.7 km s -1 ), typically observed in other Archean cratons.…”
Section: Geophysical Studies Of the Dharwar Cratonmentioning
confidence: 99%